The Lower Prevalence of Chronic Diseases Risk Factors in Vegetarian Brazilians Subjects – CARVOS Study - Julio Acosta-Navarro; Luiza A. G. Gouveia; Adriana Oki; Maria Carlos Bonfim; Carlos Hochberg; Pedro Acosta-Cardenas; George Guimarães; Raul D. Santos (International Journal of Nutrition, 2015)
Objective: To investigate the association of meat consumption with self-reported chronic diseases (heart disease, hypertension, diabetes (type I or type II) and dyslipidemia), according to demographic, social and anthropometric variables. Methods: This was a cross sectional study, conducted at the Heart Institute, University of São Paulo, with 549 adults (≥ 18 years) who answered a questionnaire to select people for The CARVOS Study (Carotid Atherosclerosis, Aortic Stiffness and Risk Factors in Vegetarians and Omnivorous Subjects). The variables analyzed were: age, gender, education level, meat consumption, self-reported coronary heart disease, hypertension, diabetes (type I or type II) and dyslipidemia, smoking and body mass index (BMI) (kg/m2). Study subjects were classified as omnivorous (OMN=consumption of meat or fish four or more times/week) (n=228, 41.5 %), semi-vegetarians (SV=consumption of meat or fish 1-3 times/week) (n=97, 17.7%) and vegetarians (VEG=no consumption of meat or fish) (n=224, 40.8%). The differences between mean values was calculated by T-ANOVA test. To test the association between the variables, chi-square test and multiple logistic regression were used (p<0.05; CI = 95%). Results: There was a greater prevalence of smokers among OM than SV and VEG respectively 56.5%, 14% and 29.4 %, p=0.009, and a higher prevalence of overweight (41.7%) in OMN in comparison with SV (29.2%) and VEG (29.0%), p=0.008. Being OM significantly increased the risk of referring hypertension, regardless of sex and age (OR 2.19; CI 95% 1.08-4.46), and was also associated with dyslipidemia, regardless of body mass index, smoking, sex and age (OR 1.78; CI 95% 1.03-3.08). Conclusion: Higher meat consumption was associated with a greater prevalence of risk factors for hypertension and dyslipidemiachronic diseases.
Keywords: Diet